Formation of the project competence of future specialists in information, library and archive services in a digital society - Прийма, Сергій Миколайович; Прийма, Сергей Николаевич; Pryima, Serhii; Anishchenko, O.; Dayong, Yuan; Ivanova, Nataliia (My University, 2019)
The article substantiates the importance of forming the project competence of future specialists in information, library and archive services with the help of the project management information systems. The essence of project development in the library sphere is specified. The key features of the project activity of specialists in information, library and archive services under the conditions of digitalization, as well as the specifics of its informatization, are analyzed. The special features of project management as a component of library management are described. Some project management information systems are characterized. The structure of library workers’ project competence (value-motivational (axiological), knowledge-content (cognitive), technological (activity-practical) components) is specified. The value-motivational component is determined by a set of stable motives (personal, cognitive, professional ones) and suggests a conscious positive attitude to the project activity automation, readiness for its implementation. The knowledge-content component assumes having knowledge of the project activity automation. The technological component includes the ability to perform the project activity automation, to feel free in the information environment, etc. The results of the experimental verification of the efficiency of pedagogical conditions in order to form the project competence of future specialists in information, library and archive services (illustrated by the implementation of the author’s special course "Information Systems for Project Management in the Professional Activities of Information, Library and Archive Specialists") are presented. The implementation of the author's special course has visualized certain positive changes in the levels of the project competence development of students in experimental groups compared with those in control ones. The results of the obtained data analysis made it possible to ascertain the positive dynamics of changes in the quantitative indicators of the levels of the project competence development of future specialists in librarianship.
Keywords: digitalization; specialists in information; library and archive services; project competence; project development; project management; methods and means of project management; project management information systems